Pengembangan Program Kegiatan dan Pendampingan Penyusunan Rencana Pembangunan Jangka Menengah (RPJMDes) Tahun 2023-2028 Desa Ulak Kembahang II - Mardalena Mardalena; Muhammad Subardin; Siti Rohima; Imelda Imelda; Ayu Sagita; Rahma Nida; Harunurrasyid Harunurrasyid (Universitas Teuku Umar, 2023)
Community Service Activities are one of the Tri Dharma of Higher Education that must be carried out, so the Service Team of the Faculty of Economics, Sriwijaya University hold a service activity in 2021 in Ulak Kembahang II Village, Pemulutan Barat District, Ogan Ilir Regency. This service activity is the provision of focus group discussion (FGD) and training in the preparation of the RPJMDes using the lecture, discussion, and questionnaire methods. The implementation of this activity is rooted in the problems faced by the Ulak Kembahang II village officials, namely the village officials still do not quite understand the importance of preparing the RPJMDes due to the lack of knowledge, skills and creativity, especially in the preparation of village programs and activities. Thus, the purpose of this activity is to carry out education and training for village officials in making RPJMDes so that village officials have knowledge and skills about making RPJMDes Ulak Kembahang II Village. The results of the questionnaire regarding the evaluation of participants' understanding of the material that had been delivered showed the participants' understanding level with an average of 82.33 percent. Thus, 29 participants in the activity consisting of 11 village officials, 4 BPD administrators, 3 LPM administrators, 4 PKK women, and 7 BUMDes administrators are expected to be able to prepare the RPJMDes of Ulak Kembahang Village II for the next period independently and participate fully in accordance with government guidelines or regulations.